Shrinking Civic Space in Africa: When Governments Crack Down on Civil Society - Smidt, Hannah (2018)
Abstract: A growing number of governments in sub-Saharan Africa are now cracking down on civil society organisations addressing human rights issues. Governments are not only shrinking the space for civic activism, but also destroying the backbone of democracy and inclusive development. In many countries in sub-Saharan Africa, civic space has been shrinking since the early 2000s - mirroring a global trend of restrictions being imposed on civil society organisations. Governments intimidate and arrest activists, and publicly criticise their advocacy work. They also promulgate restrictive policies, such as laws that curtail the foreign funding of domestic civil society groups, and resort to subtle ways of restricting civil society's operating space - for instance, via cumbersome registration processes for civil society organisations. Civil society organisations monitor and publicly expose human rights abuses. If governments commit severe abuses, they therefore have an incentive to impose restri